Nunamiut, the Tundra Dwellers - Fortescue, Michael (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2020)
This article investigates the various senses and derivations of the term nuna in the Inuit-Yupik languages in order to reveal its origin in referring to the Arctic tundra. These languages arguably derive from that of the ancestors of the earliest inhabitants of the North American tundra, other inhabitants of the circumpolar Arctic today having only moved up at later times. Likely etymological correspondences in Eurasian languages of the far north support the original meaning of the word, whose connotations can be contrasted with those of English land, by which it is usually translated. They include reference to the unique vegetation of the Arctic tundra and to settlement and migratory movements across it in the past. The word has survived through millennia as far apart as mountainous East Greenland and the Aleutian Islands chain, where it has been adapted (as Unangan tanaX) to the archipelagic setting. It is suggested that the term nunamiut, literally “tundra dwellers,” can suitably be applied to speakers of all these languages still today.